2012
DOI: 10.1038/cgt.2012.52
|View full text |Cite
|
Sign up to set email alerts
|

Human positive coactivator 4 is a potential novel therapeutic target in non-small cell lung cancer

Abstract: Transcriptional positive coactivator 4 (PC4) is a multifunctional nuclear protein that has important roles in DNA transcription, replication, repair and heterochromatinization. However, the role of PC4 in cancer remains to be clarified. Several studies propose that PC4 may act as a putative tumor suppressor. Here, we demonstrate for the first time that PC4 may represent a potential therapeutic target in non-small cell lung cancer (NSCLC). PC4 protein expression is significantly upregulated in NSCLC carcinoma t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…PC4 expression is significantly increased in NSCLC specimens compared with their adjacent non-cancerous tissues [15]. Furthermore, the downregulation of PC4 markedly inhibited NSCLC cell proliferation in vitro, and A549 cell tumorigenicity in nude mice [15]. However, whether PC4 is involved in astrocytoma remains unclear.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…PC4 expression is significantly increased in NSCLC specimens compared with their adjacent non-cancerous tissues [15]. Furthermore, the downregulation of PC4 markedly inhibited NSCLC cell proliferation in vitro, and A549 cell tumorigenicity in nude mice [15]. However, whether PC4 is involved in astrocytoma remains unclear.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, PC4 is one of the three genes that are amplified and upregulated in the SCLC cell lines [18]. PC4 expression is significantly increased in NSCLC specimens compared with their adjacent non-cancerous tissues [15]. Furthermore, the downregulation of PC4 markedly inhibited NSCLC cell proliferation in vitro, and A549 cell tumorigenicity in nude mice [15].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Expression of SUB1 was correlated with the levels of VEGF-C, VEGF-D and VEGFR-3 during the development of lymphangiogenesis and lymphatic metastasis in lung adenocarcinoma. 33 SUB1 is also shown to play a role in non-small cell lung cancer (NSCLC) 34 and astrocytoma. 35 A recent study demonstrated that SUB1 plays a role in SMYD3 mediated transactivation of growth/invasion-stimulatory genes in cancer cells.…”
Section: Introductionmentioning
confidence: 99%